Characterization of hybrid Aloe Vera/Bamboo/Palm/Kevlar fibers for better mechanical properties. (2021) - Chandramohan, D.; Dhanashekar, M.; Sathish, T.; Dinesh Kumar, S.
Abstract: An attempt was made in this study to produce natural fiber-reinforced hybrid composite material using hand-layup method. Three different natural fibers were used to strengthen Kevlar/epoxy composites. Mechanical testing was performed to characterize the composites, namely tensile, flexural, impact and double shear. The results showed that Kevlar/epoxy hybrid composite has been reinforced by Aloevera and palm with superior mechanical properties relative to other hybrid composites. The tensile strength, flexural strength and load bearing capacity were increased by 50%, 14% and 54% respectively. Fiber breakage and matrix cracking were the dominant failure mechanism of composites in tensile testing. Matrix cracking and delamination have been the dominant failure mechanism in impact testing.